Estratégias visando à melhoria da produção de etanol por Kluyveromyces marxianus pelo processo de sacarificação simultânea à fermentação de cascas de arroz - Leonel, Lillian Vieira (2020)
Rice husk is a waste derived from rice milling and is an abundant byproduct in cereal producing countries. Due to the considerable contents of cellulose in its composition, it is a potential raw material for use in various bioprocesses, such as ethanol production. However, several technical challenges must be overcome to make the second-generation ethanol production process economically viable and competitive. In this context, the process of simultaneous saccharification and fermentation (SSF), associated with the increase of solids concentration, as well as the use of surfactants in enzymatic hydrolysis in fermentation processes that employ lignocellulosic biomass are promising strategies to obtain higher sugar yields and consequently ethanol. Thus, the objective of this work was to evaluate different strategies to obtain an improvement in ethanol production from rice husk cellulose, using the thermotolerant yeast Kluyveromyces marxianus ATCC 36907. The first strategy was to carry out the fed batch SSF to increase the solids load; the second was to evaluate the effect of adding nonionic surfactants during enzymatic hydrolysis in the SSF process. First, rice husk biomass was subjected to chemical characterization for cellulose, hemicellulose, and lignin content, before and after alkaline pretreatment with 8% (w/v) sodium hydroxide (NaOH). The pretreated rice husk was subjected to enzymatic hydrolysis with different enzyme loading (5, 11, 22 FPU/gcelullose) and 10% solids (w/v) to determine the condition with increased release of reducing sugars for subsequent SSF use in batch fed with high solids loading. For the SSF in fed batch, four experiments were performed with different biomass concentrations of rice husk, being E1 and E2 experiments with initial load of 10% and final 20% (w/v) and E3 and E4 with initial load 15% and final 25% (w/v), respectively, at pH 5.5; 40 °C, 200 rpm, 96 hours. Thus, feeding intervals were established, with two feedings every 24 hours (E1 and E3) and four feedings every 12 hours (E2 and E4). As a second strategy, enzymatic hydrolysis was carried out, with the objective of evaluating the effect of different enzyme loads (5; 8; 13.5; 19 and 22 FPU/gcellulose) it was evaluated in association with Polysorbate 80 (PS80) surfactants (7.0, 10, 15, 20 and 23 mg/L), Polyethylene glycol 4000 (PEG) (0.5, 1.0, 2.0, 3.0 and 3.5 g/L) and Triton X-100 (TX-100) (75; 100; 150, 200 and 225 mg/L) in glucose release through three experiments following a central rotational composite design (DCCR) 22, including 4 axial conditions and 4 center point repetitions, totaling 12 assays for each surfactant, besides a control experiment (with enzyme addition and without surfactant), in triplicate. The third strategy consisted of adding the surfactant SSF, to evaluate the influence of the surfactant in the production of ethanol. For this, three experiments were performed: control (without surfactant + 19 FPU/gcellulose), with addition of Polysorbate 80 (10.0 mg/L + 19 FPU/gcellulose) and with Polyethylene Glycol 4000 (3.0 g/L + 19 FPU/gcellulose), the type of surfactant and respective concentrations and enzyme load selected from the results of enzymatic hydrolysis that were significant. The experiments were carried out with a solids ratio of 10% (m / v), pH 5.5, 40 °C, 200 rpm, 96 hours, in triplicate. The chemical composition of rice husk was 36.03% cellulose, 14.71% hemicellulose and 26.47% lignin and after pretreatment with 8% NaOH (w/v) the content of these fractions was 70.27; 8.39 and 21.34% cellulose, hemicellulose, and lignin, respectively. In the fed batch SSF with high solids loading, an ethanol production was obtained of 9.57; 9.92; 13.99 and 12.77 g/L, yields (YE/C) of 0.16; 0.17; 0.18 and 0.18 g/g and volumetric productivity (QP) of 0.27; 0.28; 0.39 and 0.53 g/L.h-1 for the experiments E1, E2, E3 and E4, respectively. For the enzymatic hydrolysis, glucose concentrations ranged from 32.36 to 79.57 g/L with PS80 addition, from 45.14 to 74.60 g/L with PEG and 32.28 to 47.89 g/L with addition of TX-100, while the control showed from 20.36 to 47.77 g/L in 96 hours. Only the ix surfactants PS80 and PEG in association with different enzyme loads promoted significant effects (p<0.05), the enzymatic load being the factor that most influenced the increase of final glucose production. Regarding SSF with surfactant, the addition of PS80 (10 mg/L) and PEG (3.0 g/L) in association with 19 FPU/gcellulose resulted in 6.73 and 8.17 g/L of ethanol, YE/C of 0.17 and 0.21 g / g and QP of 0.56 and 0.68 g/Lh-1 , in 12 hours of fermentation, respectively. The results suggest that rice husk is a raw material that can be used as a substrate in bioprocesses because it has a cellulose content similar to that of other lignocellulosic biomasses. The different rice husk feeding strategies used in fed batch SSF did not result in substantial increases in ethanol production. The addition of surfactants PS80 and PEG during enzymatic hydrolysis resulted in significant increases in final glucose production. In SSF, the same surfactants contributed to a slight increase in ethanol production in a shorter fermentation time, compared to the control.